Development And Validation Of RP-HPLC Method For The Estimation Of Strontium Ranelate In Sachet - K.MYTHILI; S.GAYATRI; KOYA RAVI TEJA; K.CHITRA; C.UMA MAHESWARA REDDY (International Journal of Pharma and Bio Sciences, 2011)
A rapid and sensitive RP-HPLC method with UV detection (323 nm) for routine analysis of strontium ranelate in bulk and in pharmaceutical formulation as sachet was developed. Chromatography was performed with mobile phase containing a mixture of monobasic potassium phosphate buffer and methanol (3:1 v/v) with the flow rate of 0.8 ml/min at 25 º C. In the range of 50-250 μg/ml, the linearity of strontium ranelate shows a correlation coefficient of 0.999. The percentage recovery studies were found to be in the range of 97-102 %. The proposed method was validated by determining accuracy, precision and ruggedness. The results of all the validation parameters were well within their acceptance values.